Oropharyngeal rhabdomyoma: the cause of severe sleep apnoea?. Issue 2 (9th February 2020) - Münch, Henrik Jonathan; O'Leary, Padraig; Bille, Jesper; Kjaergaard, Thomas
Abstract : This case report presents an elderly male patient who on diagnosis with a large oropharyngeal tumour had no specific symptomatology apart from severe obstructive sleep apnoea. Histopathology revealed the tumour to be an adult rhabdomyoma, a rare but benign tumour arising from striated muscle cells. The tumour obstructed most of the oropharyngeal space and almost occluded the patient's airway when lying in a supine position. The patient was deemed operable, and the tumour was excised in toto using a transoral robotic surgery system. On follow-up, the patient had a severe reduction of apnoeas/hypopnoeas and felt subjectively 'reborn'. This is to our knowledge the first case where an adult rhabdomyoma is removed using a robot-assisted approach, thus presenting a new and viable option when considering removal of benign tumours of the pharynx leading to a very minor degree of morbidity for the patients.